Caracterização agronômica e postulação de genes de resistência à ferrugem do colmo em genótipos de trigo parcialmente resistentes à ferrugem da folha - Casassola, Alice (2012)
With the increasing of the population and the losses caused by diseases in major crops of global importance, the advancement of the genetic breeding has become vital. Considering the wheat, grain yield and resistance to leaf and stem rust are some characteristics with greater focus. Appropriate agronomic characterization and genotypic characterization of resistance genes present in the germplasm, provide essential information, facilitating the work of the breeders in the choice of parental and, consequently, reducing the time of obtaining cultivars with durable resistance and high yield. Thus, this study aimed to evaluate phenotypically and to characterize genetically, for the genetic similarity and presence of resistance genes to stem rust, cultivars and lines developed by the program for genetic improvement of wheat from the Brazilian Agricultural Research Corporation - Embrapa Wheat. The molecular analyzes were conducted at the Laboratory of Biotechnology and the agronomic evaluations were conducted in a growth chamber and greenhouse at Embrapa Trigo. The characterization for resistance to stem rust had been carried out in experimental fields of the Kenya Agricultural Research Institute (KARI) in Kenya, Africa, in collaboration with the International Center for Maize and Wheat Improvement - CIMMYT and Embrapa Wheat. Thirty genotypes were used for the agronomic characterization and analysis of genetic similarity. Of these, the lines PF 9027, PF 950351, PF 030132, PF 979002, PF 040488 and IWT 04019 showed agronomic traits suitable to the standards required by the breeding program of the Embrapa Wheat and presented genetic variability. The other genotypes may be used in varietal improvement, but require a pre-breeding stage. Considering the methodologies for detecting the resistance gene to stem rust, Sr31, the use of the J071 and SCM9 microsatellite markers associated with genomic hybridization in situ (GISH) gave satisfactory results. These data also showed that the implementation of this strategy is feasible to use routinely in the Biotechnology Laboratory, which, in turn, detected the presence of the gene Sr31 in 37% of the germplasm studied. Thirty seven genotypes were evaluated to resistance to stem rust and postulation of stem rust resistance genes. Six specific Sr genes molecular markers were used for the postulation. Of these genotypes, nine were resistant or moderately resistant to stem rust and 16 were moderately susceptible, representing 67.5% of the total. However, none of the genes identified was totally responsible to explain the resistance, since effective genes present in resistant genotypes were also present in susceptible ones.